Architecture, heritage, history, memory - Lipman, Alan (Acta Structilia, 2004)
... when the modern world finds that the eclecticism of the present is barren and fruitless, and that it needs and will have a style of architecture which ... can only be as part of a change as wide and as deep as that which destroyed Feudalism; when it has come to that conclusion, the style of architecture will have to be historic in the true sense; it will not be able to dispense with tradition; it cannot begin at least without doing something quite different from anything that has been done before; yet whatever the form of it may be, the spirit of it will be in sympathy with the needs and aspirations of its own time, not simulations of needs and aspirations passed away. Thus it will remember the history of the past, make history in the present, and teach history in the future. (William Morris, 1889 in Cole, ed.,1944, p. 492)